Comparative determination of human health risks associated with consumption of groundwater contaminated with lead in selected areas surrounding the former lead mine in Kabwe and non-mining areas in Lusaka, Zambia - Siame, Tasha; Muzandu, Kaampwe; Kataba, Andrew; M’Kandawire, Ethel (International Journal Of Community Medicine And Public Health, 2023)
Background: This study focused on addressing health risks attributed to lead (Pb) contamination in groundwater, prompted by its known connection to negative health outcomes. It investigated the extent of Pb exposure through groundwater consumption near areas surrounding the former lead mine in Kabwe and non-mining areas in Lusaka, Zambia. The study compared the health risks of consuming Pb-contaminated groundwater in Kabwe's mining vicinity and Lusaka's non-mining areas. Methods: A comparative cross-sectional study collected 61 borehole samples from both areas and analyzed Pb levels using atomic absorption spectrometry. Health risks were evaluated via estimated daily intakes (EDI), target hazard quotient (THQ), and target cancer risk (TCR) assessments. Statistical analysis employed the Mann-Whitney U test due to non-normal data distribution. Results: Pb concentrations were significantly higher (p<0.05) in mining areas (median=0.131 mg/l) than in non-mining areas (median=0.071 mg/l). Alarmingly, 91% of mining and 74% of non-mining samples exceeded world health organization limits. Particularly, EDIs for adults and children from mining areas exceeded recommended intakes. However, THQs were <1, indicating no immediate adverse health effects. Equally important, TCRs fell within USEPA's acceptable range, suggesting negligible cancer risk associated with Pb exposure. Conclusions: The elevated EDIs in both mining and certain non-mining areas suggest potentially toxic health effects. Notably, the THQ values below 1 imply no immediate health risks. TCRs within acceptable limits underscore a minimal cancer risk. As a result, addressing elevated Pb levels in groundwater is critical in both study areas to mitigate potential health effects associated with Pb exposure.